Electron Fluxes in Biocathode Bioelectrochemical Systems Performing Dechlorination of Chlorinated Aliphatic Hydrocarbons - Chen, Fan; Li, Zhiling; Yang, Jiaqi; Liang, Bin; Huang, Cong; Cai, Weiwei; Nan, Jun; Wang, Aijie (Frontiers in Microbiology, 2018)
Bioelectrochemical system (BES) is regarded as a promising approach for the enhanced dechlorination of chlorinated aliphatic hydrocarbons (CAHs). However, the electron distribution and transfer considering dechlorination, methanogenesis and other bioprocesses in these systems are little understood. This study investigated the electron fluxes in biocathode BES performing dechlorination of three typical CAHs, perchloroethylene (PCE), trichloroethene (TCE) and 1,2-dichloroethane (1,2-DCA). It is found the constructed biocathode at –0.26 V had significantly higher dechlorination efficiency (E24h > 99.0%) than the opened (E24h of 17.2-27.5%) and abiotic cathode (E24h of 5.5-10.8%), respectively, indicating the enhanced CAHs dechlorination capacities. Cyclic voltammetry analysis demonstrated the enhanced cathodic current and the positive shift of onset potential in cathodic biofilm. Under autotrophic cathode, CAHs dechlorination capacities were still maintained, verifying cathodes could be utilized as the sole electron donor (columbic efficiencies of 80.4-90.0%). Cis-1,2-dichloroethene was the primary product for PCE and TCE, and while, 1,2-DCA went through the different dechlorination pathway with the non-toxic ethene as the final metabolite. Methane was the main by-product of heterotrophic biocathode, and methane production could be enhanced to some extent by electrochemical stimulation. The various electron fluxes originating from cathode and acetate might be responsible for the enhanced CAHs dechlorination, and while, methane generation and bacterial growth would probably reduce the fraction of electrons provided for CAH dechlorination. The study is the first to reveal the dechlorination and competitive bioprocesses in CAH-dechlorinating biocathodes from the perspective of electron fluxes.